Килимарство й виробництво з вовни у кримських татар - Акчуріна-Муфтієва, Н. (Народна творчість та етнографія, 2007)
The question of Crimean Tatar carpet weaving and wool production is revealed in the article: kilims, pile, coarse cloth, torba (bag) and turncoat. Considerable attention is paid to typology of Crimean pileless carpets. Three types are pointed out: “Orta” (the middle), “Kobekli-orta” (middle umbilical), “Namazlik” (carpets for praying). Ornamental structures of Kilims are examined, the names of ornamental tendencies, the material used and colour gamut are re-established. The author brings us to conclusion that the most ancient and traditional Crimean Tatar art is production of pile bat carpet weaving existed only in very narrow frame of space and time.